THE SEDIMENTOLOGY OF THE LOWER PERMIAN DANDOT FORMATION: A COMPONENT OF THE GONDWANA DEGLACIATION SEQUENCE OF THE SALT RANGE, PAKISTAN (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2016)
The Dandot Formation is a part of the Lower Permian, dominantly continental, Gondwanan Nilawahan Group in the Salt Range, Pakistan. The formation conformably overlies the glacio-fluvial Tobra Formation and has a sharp conformable contact with the overlying fluvio-continental Warchha Sandstone. Sedimentary analyses show that the Dandot Formation consists of: 1. bioturbated sandstone lithofacies (L1), 2. dark green mudstone/shale lithofacies (L2), 3. flaser bedded sandstone lithofacies (L3), 4. rippled sandstone lithofacies (L4), 5. cross-bedded sandstone lithofacies (L5), and 6. planar sandstone lithofacies (L6). These can be grouped into shoreface, inner shelf, and tidal flat and estuarine facies associations, deposited in shallow marine to intertidal environments. The upper part of the Tobra Formation at the Choa-Khewra road section, where it conformably underlies the Dandot Formation, contains palynomorphs assignable to the earliest Permian 2141B Biozone. In south Oman, the 2141B Biozone is closely associated with the Rahab Shale Member, a widespread shale unit which is considered to represent part of a Permian deglaciation sequence which culminates in the marine beds of the Lower Gharif Member, interpreted as due to post glacial marine transgression. Thus, the Tobra Formation and the overlying marine Dandot Formation may form part of a similar deglaciation sequence.